Measurements of acoustics properties for level-dependent ear-muffs - Puto, D.; Kotarbińska, E. (Archives of Acoustics, 2003)
The aim of this paper is to present methods of acoustic measurements of level-dependent ear-muffs with an electronic sound restoration system switched off and on, according to EN 352-4. Measurements of sound attenuation and H, M, L criterion levels were carried out for a model of a level-dependent earmuff. The acoustic properties of test sites, sound field requirements and test signals are discussed. Measurements of sound attenuation were carried out in a chamber for testing hearing protectors. The chamber fulfilled the requirements of PN-EN 24869-1. Measurements of the H, M, L criterion levels were carried out in a reverberation room where the sound field of the test site complied with the requirements specified in ISO/DIS 11904-1. Both the chamber for testing hearing protectors and the reverberation room are the part of the laboratory of noise in the Central Institute for Labour Protection in Warsaw, Poland.